Quantifying the role of iron recycling by Adélie and Emperor penguins over the austral spring and summer in Prydz Bay - Ratnarajah, Lavenia; Emmerson, Louise; Southwell, Colin; Lannuzel, Delphine; Townsend, Ashley T.; Bowie, Andrew R. (Frontiers in Marine Science, 2024)
In large areas of the Southern Ocean, iron limits phytoplankton production. Although biologically mediated iron recycling has been studied for the higher trophic-level whales and the lower trophic-level krill, less is known of the numerically abundant seabirds foraging in Antarctic waters. In this study, we estimate the magnitude of iron recycled by two Antarctic breeding seabirds, the Adélie and emperor penguins, across the austral spring and summer in the Prydz Bay region, East Antarctica. Their contribution to iron recycling and associated pathways differs in line with their contrasting life history strategies (summer and winter breeding) and their breeding habitat (land and fast ice). We consider their breeding cycle in relation to their terrestrial activities compared to foraging periods at sea. High iron concentration ( 419 mg kg−1) in guano of both penguin species suggests that they are a source of regenerated iron. Breeding emperor penguins supplied an average of 237 μmol iron m−2 day−1 on the fast ice that they breed on that eventually ends in the ocean when the ice melts completely in summer (November–February). During their foraging trips, the adult emperor penguins contribute between 7 × 10−5 and 4 × 10−4 μmol iron m−2 day−1, as their foraging ranges increase over the breeding season. In contrast, breeding Adélie penguins supplied between 254 and 1,243 μmol iron m−2 day−1 whilst at their colony, with a fraction of guano entering the ocean via meltwater flowing into the ocean. The flux decreases to 2 × 10−3 to 6 × 10−2 μmol iron m−2 d−1, whilst they are foraging. Our study finds that penguins redistribute a large flux of iron onto their colonies, which may enter the adjacent water through sea ice melt and facilitated through katabatic winds. Despite their high abundance in Prydz Bay, the contribution of penguins to iron flux during their foraging periods is minor, due to the enormous foraging range being covered. Further research into the bioavailability of iron by marine organisms coupled with parallel measurements of seawater iron concentration and phytoplankton uptake experiments will be invaluable in refining iron budgets in both this region and other hotspots along the Antarctic coast where higher trophic-level animals are abundant.